Alcohol: is it detrimental to HIV infected individuals on antiretroviral therapy? - Joshi, Kavita S.; Chavan, Gajanan (International Journal of Research in Medical Sciences, 2017)
Background: Chronic Alcohol consumption is immunosuppressant and HIV causes immunodeficiency. Both in same patient can have detrimental effect. HIV can progress rapidly in an alcoholic patient. This study is looking for adverse effects of alcoholism on CD4 response, adherence and adverse drug reactions on patients who are on highly active antiretroviral therapy. Methods: A prospective observational study done over period of one year after local institutional ethics committee approval was obtained. All consecutive HIV infected male patients presenting for first time and indicated to start on HAART above age of 18 years who were willing to give consent were recruited for this study. Patients with Hepatitis B and Hepatitis C were excluded from the study. Results were analyzed using ANOVA and paired T test. Results: The CD4 counts remained lower in habitual alcoholics compared to social alcoholic and nonalcoholic study groups, P value being 0.0385 (habitual alcoholic); 0.0291 (social alcoholic) and 0.0251 (non-alcoholic) respectively. It was found (13%) alcoholic patients; 12 (8%) social alcoholic and 4 (2.7%) Non-alcoholic patients were not maintaining pill counts. 36 (24.5%) of total Patients were not maintaining pill counts. Patients consuming alcohol even did not follow up nor followed instructions, P value being 0.000. Conclusions: Alcoholic patients were not following regularly for treatment. Hence we can conclude that alcohol has negative effect on adherence to HAART. Therefore in our part of country alcoholics should be considered as high risk groups for HIV care.